RETRACTED: Modeling of the process of retaining the concentration of aggressive gases during the operation of deaerators - Khuzhakulov Saydullo; Murodov Ismoildjon; Uzbekov Mirsoli; Meyliev Laziz; Pardaev Zokir (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 549, 00001 (2024), https://doi.org/10.1051/e3sconf/202454900001